School of Middle Eastern languages - A. V. Shtanov (Vestnik MGIMO-Universiteta)
School of Middle Eastern languages (Arabic, Hebrew and Turkish), as well as a number of languages of the Caucasus and Central Asia (Azerbaijan, Uzbekistan, Turkmenistan) is based on the intellectual heritage, tracing its history to the Department of Arabic Studies, established in 1871-1872 years when Lazarev Institute of Oriental Languages. The department provides a high level of theoretical and practical teaching of modern Arabic literary language and the spoken language of a number of Arab countries. Department annually produces 20-25 international affairs Arabists working in international, political, economic, legal, journalistic and other areas in the Russian Federation, the CIS countries and abroad.